2013
DOI: 10.1002/jgrc.20303
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the deep Southern Ocean (1958–2010): Implications for Antarctic Bottom Water properties and volume export

Abstract: [1] Regional formation of deep and bottom water masses around the Antarctic continental shelf is one of the most important processes contributing to variability of the global meridional overturning circulation deep cell. Southern Ocean hydrographic data collected during the years 1958-2010 indicate that dense shelf waters cooled and freshened during that period. In the surrounding open ocean, Antarctic Bottom Water (AABW) warmed, with no evidence of salinity change. As a result of source-water property changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
83
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 77 publications
16
83
1
2
Order By: Relevance
“…In concordance with these findings, a decrease in the WSBW's contribution (∼ 20 %) to the total water mass mixture in the Weddell Basin occurred in the 1980s and 1990s near the Greenwich Meridian and at the tip of the Antarctic Peninsula (Kerr et al, 2009a). More recently, Azaneu et al (2013) fully investigated the most complete Southern Ocean data set available and found a reduction in the volume of AABW in addition to warming and decreasing density from 1958 to 2011 in the deep and bottom layers south of 60 • S. Despite the reported freshening of the AABW layer at the Drake Passage during the period 1993-2010 (Jullion et al, 2013), no sign of this freshening trend was found by Azaneu et al (2013) in WSDW/WSBW layers in the last 50 years in the inner Weddell Sea. In a global context, the AABW's layer in the global basins underwent a contraction from the 1980s to the 2000s (Purkey and Johnson, 2012).…”
Section: T S Dotto Et Al: Weddell Sea Water Masses In Distinct Ocesupporting
confidence: 66%
See 3 more Smart Citations
“…In concordance with these findings, a decrease in the WSBW's contribution (∼ 20 %) to the total water mass mixture in the Weddell Basin occurred in the 1980s and 1990s near the Greenwich Meridian and at the tip of the Antarctic Peninsula (Kerr et al, 2009a). More recently, Azaneu et al (2013) fully investigated the most complete Southern Ocean data set available and found a reduction in the volume of AABW in addition to warming and decreasing density from 1958 to 2011 in the deep and bottom layers south of 60 • S. Despite the reported freshening of the AABW layer at the Drake Passage during the period 1993-2010 (Jullion et al, 2013), no sign of this freshening trend was found by Azaneu et al (2013) in WSDW/WSBW layers in the last 50 years in the inner Weddell Sea. In a global context, the AABW's layer in the global basins underwent a contraction from the 1980s to the 2000s (Purkey and Johnson, 2012).…”
Section: T S Dotto Et Al: Weddell Sea Water Masses In Distinct Ocesupporting
confidence: 66%
“…All reanalyses examined showed a γ n decreasing trend for WOCE SR4 (except for the SODA product; Table 4). AABW observations showed a warming trend for the global AABW exported from the Southern Ocean and a reduction in its volume (e.g., Johnson, 2010, 2012;Azaneu et al, 2013). The latter may be a consequence of the downward trend in AABW density, although no sign of freshening has been found in the inner Weddell Sea (Azaneu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since no real open ocean polynya has been reported for this period, a critical analysis of the model mechanisms of heat exchange between the surface waters and sea ice is required in the future to efficiently understand the role of WDW in open ocean polynya establishment. In addition, since bottom layer warming and intermediate layer cooling are the possible mechanisms that diminished stratification in ECCO2, further evaluation of the causes of those trends (Azaneu et al, 2013) is needed to understand the primary factors leading to the weak ocean surface stratification. Finally, the appearance of a real open ocean polynya in October 2016 and September 2017 in the Weddell Sea will also furnish a study scenario to understand heat exchange between sea ice and warmer waters, and to compare with ocean reanalysis products.…”
Section: Discussionmentioning
confidence: 99%